2017
DOI: 10.2174/1389201018666171004144615
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cinnamyl and Caffeoyl Derivatives of Cucurbitacin-Eglycoside Isolated from Citrullus colocynthis Fruits and their Structures Antioxidant and Anti-inflammatory Activities Relationship

Abstract: These results suggested that mechanistic-based evidence substantiating the traditional claims of cucurbitacin E glucoside (1) and its derivatives (2 and 3) to be applied for the treatment of inflammation-related disorders, such as oxidative liver damage and inflammation diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As an extension of our studies on medicinal chemistry research of some new biologically active natural products (El-gizawy and Hussein 2017; Hussein et al. 2017), we now report the biological activities, isolated compounds and HPLC profile of V. nubicum which might contain compounds with promising antioxidant, anti-inflammatory and antiulcerogenic activities.…”
Section: Introductionmentioning
confidence: 89%
“…As an extension of our studies on medicinal chemistry research of some new biologically active natural products (El-gizawy and Hussein 2017; Hussein et al. 2017), we now report the biological activities, isolated compounds and HPLC profile of V. nubicum which might contain compounds with promising antioxidant, anti-inflammatory and antiulcerogenic activities.…”
Section: Introductionmentioning
confidence: 89%
“…RNs include oxidatively active free radicals and nitro compounds produced by the interaction of ROS with nitric oxide (NO), mainly including NO and peroxynitrite (ONOO-). The antioxidant system consists of two major parts, enzyme antioxidants (including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)) and non-enzymatic antioxidants (Hussein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al (2019) showed that pretreatment with cucurbitacin-rich extract of Cucumis melo L. inhibited phenylephrine-mediated vasoconstriction, enhanced acetylcholine-mediated vasodilation, and suppressed the angiotensin II-induced increase in systolic blood pressure in mice. Furthermore, antiinflammatory and antioxidant effects of CuE were observed in carrageenan-induced paw edema and liver damage animal models (Peters et al, 1997;Hussein et al, 2017). Cell culture studies revealed the neuroprotective effects of CuE against 1methyl-4-phenylpyridinium (MPP + ) induced Parkinson's disease by modulating lysosomal-autophagic mechanisms (Arel-Dubeau et al, 2014).…”
Section: Introductionmentioning
confidence: 99%